Role of Family Upbringing in Preparing Girls for the Marital Life Requirements in Contemporary Saudi Society: A study on a sample of newly married women in the Kingdom of Saudi Arabia from the different the western, eastern, southern, and northern regions - Afghani, Amani Abdulaziz (Journal of Humanities & Social Sciences, 2023)
This study aims to study family upbringing and its dimensions (methods of family upbringing - attitudes gained from family upbringing - parents’ practices in their family life), and marital requirements and their themes (marital education - awareness of marital problems, skills and values in marital life). It also aims to give suggestion for proper marital family upbringing and proper preparation for marriage from the girls’ point of view and studying the linkage between family upbringing and its themes, marital requirements and its themes, and some socio-economic variables as well as studying the differences in family upbringing and its themes, marital requirements and their themes according to the duration of marriage of the origin family and the level of education of the research sample. The study follows the descriptive method. The study sample consists of 242 newly married women (five years of marriage or less) who have been chosen by chance. Data has been collected through a questionnaire and distributed electronically through social networking sites. The study reached many findings the most important of which is that there is a statistically positive correlation between the variable of parental interaction practices and the marital requirements variables and their overall score at the statistical significance level of (0,001). And between the whole family upbringing variable and the marital requirement variables and its overall score of at a statistical significance level of (0,001). This indicates that the higher the family upbringing level and its themes, the higher the awareness of marital requirements and its themes.